HUMAN RIGHTS AND CONFUCIAN VALUES: A CRITIQUE OF A FALSE DICHOTOMY - Ivana Buljan (Asian and African Studies)
Although human rights are often taken for granted as universal values, intercultural dialogue re garding human rights is characterized by a philosophical discourse that lacks real theoretical fou ndations. This article argues that the advancement of intercultural discourse regarding human ri ghts should avoid the persistent fallacy of a “false dichotomy” which assumes Chinese and Western values as alternatives. Firstly, I address the main problems in the intercultural dialogue regarding human rights. Secondly, I explore the core problem, i.e. the issue of the compatibility between the Confucian values and human rights. I point out that human rights are based on a specific under standing of a person as an autonomous rational being who is the bearer of abstract moral duties. T he Chinese tradition is grounded in a different understanding of the individual and the communi ty’s fundamental ethical and political values, where an individual realises his/her potential. In par ticular, the Confucian concept of self and derived relational values, such as harmony, filial loyalty, righteousness and ritual, are fundamental conflicting elements regarding the conception of human rights. Despite Confucian ethics not being based on the conception of the person as an autonomous individual, I argue that many of the concepts within Confucian ideas align with the ideas presented in human rights conventions.